Neuroprotective effects of arctigenin on cerebral ischemia-reperfusion injury in rats via the EPO/EPOR-JAK2-STAT5 signaling pathway - Xu, Shanshan; Chen, Yuting; Zhang, Lingling; Lu, Wei; Chen, Xu; Wang, Ting; Wang, Wenjie (Frontiers in Pharmacology, 2025)
IntroductionCerebral ischemia-reperfusion injury (CIRI) is a complex pathophysiological process with significant morbidity and mortality, and there is no specific agent. Previous studies have found that arctigenin can play an anti-CIRI role through anti-inflammatory and antioxidant effects. This study further explored the anti-CIRI mechanism of arctigenin via the EPO/EPOR-JAK2-STAT5 signaling pathway.MethodsTTC and H&E staining were used to observe infarct volume and morphological changes in the brain, RT-PCR was used to detect EPO, EPOR, HIF, JAK2, STAT5, NF-κB mRNA expression, EPO/EPOR ratio was detected by immunofluorescence, and HIF was observed by immunohistochemical staining. The protein expression levels of JAK2 and STAT5 were detected, and the protein expression levels of EPO, EPOR, HIF, JAK2 and STAT5 were detected by western blot.ResultsOur results indicate that arctigenin significantly reduced infarct volume and improved histopathological changes in the brain tissues from CIRI rats at 24 h, 48 h, and 72 h after reperfusion by TTC and H&E staining. RT-PCR analysis showed that arctigenin could significantly upregulate the mRNA expressions of EPO, EPOR, and HIF and downregulate the mRNA expressions of JAK2, STAT5, and NF-κB in the brain tissues from CIRI rats at 24 h, 48 h, and 72 h after reperfusion. Immunofluorescence assay showed that the ratio of EPO/EPOR in CIRI rats at 24 h, 48 h, and 72 h post-reperfusion was significantly elevated by arctigenin. Arctigenin could upregulate the HIF protein expression while downregulate the protein expressions of JAK2, STAT5, and NFκB in the brain tissues from CIRI rats at 24 h, 48 h, and 72 h after reperfusion by immunohistochemical staining. The protein regulation results of EPO, EPOR, HIF, JAK2, and STAT5 were also confirmed by Western blot at 72 h after reperfusion, consistent with the above results.DiscussionIn conclusion, arctigenin demonstrated neuroprotective properties against CIRI potentially through the EPO/EPOR-JAK2-STAT5 signaling pathway. These findings provide a scientific rationale for further exploration of arctigenin as a therapeutic agent for stroke.